Gender differences in operational and cognitive abilities - Lager, Emil; Sorjonen, Kimmo; Melin, Marika (Frontiers in Psychology, 2024)
Introduction: Gender differences in cognitive and operational abilities have been identified. Yet, their interrelationship remains underexplored. This prevents tailored evidence-based selection, allowing discrimination to persist. Method: Data from a test battery of operational and cognitive tests was analyzed. In total 2743 aviation pilot candidates' test scores were analyzed. Results: Males had a significantly higher score on mental spatial ability, memory retention, abstract problem solving, multitasking ability (MU), and manual spatial ability (MSA); and females on perceptual speed. Correlations between MU and MSA (difference = 0.269 (95% CI: 0.114; 0.405)) and between MSA and perceptual speed (difference = 0.186 (95% CI: 0.027; 0.332)) were significantly stronger among female applicants. A high MSA score was more predictive of a high score on MU, Perceptual speed, and Memory for female compared with male applicants (p < 0.002 for the MSA score × sex interaction effect in all three cases). Discussion: Interpretation of test scores in between genders potentially may need to look different for final selection decisions for operational professions, as female test profiles were shown to exhibit greater homogeneity.